Dari Tradisi Klasik ke Kontekstualisasi Modern: Tinjauan Literatur atas Dinamika Pertumbuhan Studi Al-Qur'an - Achmad Muzaqi; Aliya Zulva Ahsani; Anggraini Citra Fatmala; Mohamad Salik (Jurnal Budi Pekerti Agama Islam, 2026)
The discipline of Qur'anic Studies (‘Ulūm al-Qur’ān) has experienced a significant paradigm shift from the classical textual-normative approach to a modern contextual and hermeneutic framework. This systematic literature review aims to map the dynamics of this growth by evaluating the ontological, epistemological, and teleological boundaries of Qur'anic studies within contemporary Islamic scholarship. Utilizing a qualitative Systematic Literature Review (SLR) design, data were gathered from reputable academic journals published over the last decade and analyzed through thematic synthesis. The findings reveal four major transformations. First, an ontological redefinition where the Qur'an is no longer viewed merely as a static written text, but as a performative living discourse, necessitating a strict demarcation between the Qur'an and Hadith to prevent the sacralization of the profane. Second, an epistemological reconstruction that shifts the discipline from mechanistic auxiliary sciences to a holistic-interdisciplinary methodology integrating social sciences and humanities. Third, an expansion of scope beyond textual analysis into applied realities, notably the emergence of Living Qur'an and Digital Qur'an sub-disciplines responding to the disruption of religious authority. Fourth, a teleological shift where the ultimate goal of studying the Qur'an transitions from individual piety to social transformation, serving as an intellectual defense mechanism against post-truth populism and promoting emancipatory theology. The implication of this study suggests that contemporary Qur'anic studies must proactively offer ethical frameworks for global challenges rather than merely preserving historical dogma